Performance evaluation of a novel adjustable lampshade-type reflector (ALR) in indoor farming practice using choy sum (Brassica rapa var. parachinensis) - Huang, Jim Junhui; Guan, Zijie; Hong, Xiaotang; Zhou, Weibiao (Frontiers in Plant Science, 2023)
The retrieval of lost light energy for promoting vegetable development could be a challenge in indoor farming practice yet little is attempted so far. In this study, the performance of a novel adjustable lampshade-type reflector (ALR) was executed, for evaluating the feasibility of applying such a device in indoor farm racks (IFR). This application targeted at reflecting stray light back to the IFR for improving the growth and quality of leafy vegetable choy sum (Brassica rapa var. parachinensis). The optimal configuration of ALR was firstly confirmed via simulations using TracePro software. The combination of an included angle at 32° and a reflective board width of 10 cm, under 12 cm of distance between light sources and germination tray surface, was revealed to achieve the cost-optimal reflective effect. The simulation-based ALR was subsequently custom-built for actual performance validation. It was shown to effectively produce uniform distributions of temperature, relative humidity and photosynthetic photon flux density (PPFD), as well as to accumulate more photosynthetic photon energy density (PPED) along a cultivation shelf. Compared with the control where no ALR was used, fresh and dry weights of choy sum shoots cultivated using an ALR were increased by up to 14% and 18%, respectively. In addition, their morphological traits were found to be more uniform. Furthermore, their total carotenoid level was enhanced by up to 45% while the chlorophyll b level was markedly decreased. However, no statistically significant difference was found in total phenolic content and antioxidant capacity across the shelf, indicating that the ALR application led to more uniform antioxidant-related quality of choy sum shoot. ALR application in IFR can thus effectively boost vegetable production and result in quality improvements under the identical amount of electricity consumption in indoor farming, as compared to ALR-free control.